Distribution ceremony on breeding bucks for Khawateen goat keepers - CM News (CM News, 2017)
Distribution Ceremony on Breeding Bucks for Khawateen Goat Keepers . by *** USAID , ILRI , KWC , PARC *** ** We welcome** 1 Professor Dr. M.N. M. Ibrahim ** ILRI , country representatives Pakistan. and ** Zeshan Mustafa ** 2- Prof. Dr. Mohammad Sajjad Khan ** Dean faculty of Animal Sciences / University of Agriculture Faisalabad. 3. Dr. Jauhar Ali ** Member Animal Sciences Pakistan Agriculture Research Center Islamabad. 4- Mr. Dilawar Hussein ** SDO Sericulture Multan . 5- Dr. rbnuaz Khan ** Director Life stock Bahawalpur 6. Malik Usman Rashid Bobak **Chairman municipality Ahmadpur East.